Some Functional Properties of Blondo-Calcium Mix - Hani Putranto; Slamet Sudarmadji (Indonesian Association of Food Technologists, 1994)
Blondo is a solid residue of the wet coconut milk oil extraction process. The oil extraction from coconut milk, which is facilitated by adding Ca2SO4, produced blondo-calcium mix residue. This residue was studied for its stability as a high protein food ingredient. Blondo-calcium mix contains 77.6% protein with water retention capacity of 2 ml water/g (less than skim milk powder but greater than casein) and oil retention similar to those of skim milk powder or casein. The emulsion capacity of blondo-calcium mix was slightly lower (70%) than that of skim milk powder or casein at pH 6 and 8 but slightly higher at pH 2 and 10. The emulsion stability of blondo-calcium was lowest at pH 4 and 6, but highest at pH 2. Blondo-calcium mix is probably best to be used in a low pH food emulsion system (such as in non-dairy yogurt)